Great Power Relations in Argentina, Chile and Antarctica - Morris, Michael A. author. aut Link
X, 210 p.
Keywords: This collection of papers looks at international relations in Argentina, Chile and Antarctica. Michael A.Morris is also author of "Expansion of Third-World Navies", "International Politics and the Sea" and "The Strait of Magellan and the Southern Ocean".